FIELD SCREENING OF SUGARCANE CLONES AGAINST THE INTERNODE BORER, Chilo sacchariphagus indicus - PASUPATHY, S.; SHANMUGANATHAN, M.; RAVICHANDRAN, V.; BABU, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Reaction of Advanced Yield Trial (AYT) clones were screened for their resistance reaction against internode borer, INB Chilo sacchariphagus indicus at Sugarcane Research Station, Tamil Nadu Agricultural University, Cuddalore, Tamil Nadu during December, 2019-20 and May, 2020-21. Results revealed, out of 30 AYT clones and a standard variety CoC 24 the mean percent internode borer, Chilo sacchariphagus indicus damage was ranged from the minimum of 2.1 (C 15645) percent to the maximum of 43 (C 15181) percent. In the advanced yield trial (AYT) (29) clones are less susceptible to internode borer, Chilo sacchariphagus indicus. The clone C 15004 was moderately susceptible (MS) during 2019-20 seeing for INB resiotance. In another screening experiment during 2019 July there were 20 Advanced yield trial (AYT-II) clones and two standard varieties were studied for INB resistance and infestation intensity. The mean percent INB damage was ranged from 2.4 (C 16353) to the maximum of 52.5 (C 16122). Out of 20 AYT-II clones, nineteen clones viz., C 16415, C 16276, C 16021, C 16335, C 16183, C 16035, C 16418, C 16086, C 16282, C 16331, C 16338, C 16031, C 16034, C 16097, C 16038, C 16108, C 16137, C 16353 and C 16270 and the standard varieties Co 86032 and CoC 25 were under Less susceptible grade (LS). The mean percent internode borer, Chilo sacchariphagus indicus infestation intensity was ranged from the minimum of 12 (C 16035) to the maximum of 66.8 (C 16335). During 2020-21, May month advanced yield trial (AYT) sugarcane clones (22) and three standard varieties, put together 25 entries were planted in Randomized Block Design with two replications against the internode borer, Chilo sacchariphagus indicus. The observations on the sugarcane internode borer damage was followed as done in 2019-20 season experiment. Out of 25 entries, 18 clones were less susceptible to internode borer. Less susceptible clones are: C2016-031, C2016-035, C2016-038, C2016-069, C2016-086, C2016-097, C2016-108, C2016-122, C2016-183, C2016-261, C2016-270, C2016-282, C2016-304, C2016-331, C2016-337, C2016-338, C2016-415, C2016-418 and a standard variety Co 86032.